The Role and Applications of Aerogels in Textiles - Farooq Azam; Faheem Ahmad; Zeynep Ulker; Muhammad Sohail Zafar; Sheraz Ahmad; Abher Rasheed; Yasir Nawab; Can Erkey (Advances in Materials Science and Engineering)
Textiles have been used for clothing purposes since ancient times. However, due to their functional properties, their importance—as well as their use in various fields such as filtration, protective clothing, and medical applications—increased over time. Properties of the textile fabrics depend mostly on the fiber type, fabrication technique, and structure. Moreover, fabric porosity is one of the properties that provide comfort, increased thermal insulation, and filtration capability to the end products. The porous structure of woven, knitted, and nonwoven fabrics has been used for many years to get the desired porosity. Usually, macroporous structures are achieved using these types of textiles. Electrospinning is used to produce nanoporous textile fibrous web, but its poor mechanical properties and low production rate limit its use. Aerogels are solid materials with ultrahigh porosity at the nanoscale with low density and good thermal insulation properties, due to which they are considered potential insulation materials today. On the other hand, pure aerogels are sometimes brittle and have poor mechanical properties. Thus, they cannot be directly used in various applications. Consequently, textile reinforced aerogel composites have been developed, which could provide flexibility and strength to aerogels and impart nanoporous structure to textiles. This review summarizes conventional techniques to produce the porous structure in textiles followed by the modern techniques to develop a nanoporous structure. Further, different mechanisms to synthesize textile reinforced aerogel composites are discussed to get a nanoporous structure for filtration and thermal insulation applications. The porosity, mechanical properties, and thermal insulation of textile reinforced aerogel composites are also highlighted. In the end, we give a conclusion that not only summarizes the literature, but also includes recommendations for the researchers.